Amulets need attention! Returning to the classifications to better understand the characteristics of the small finds of Tell el-Ghaba (North Sinai, Egypt) - Calomino, Eva Amanda (2021)
Much of the historical-archaeological approaches integrate conceptualisations and classifications for data management, databasecreation and their submission under qualitative and quantitate analyses. Throughout this classification process, the artefacts areincluded in categories that generally correspond to previously used names within disciplinary traditions specific to each area ofstudy. In this sense, these categories sometimes have explicit definitions and sometimes do not, hence continuing with the lack ofproblematisation of the assumptions that said categories entail. In this way, concepts begin to work as ?labels? that integrate socialand functional assumptions and broader meanings. The categories tend to become diffuse, and, as such, their explanatory powerdecreases. Something similar has happened with the concept of ?small finds? in the research from archaeological sites in Ancient Near East. A way to remedy this situation is proposed here by presenting a definitive classification proposal for the small finds recoveredfrom Tell El-Ghaba (north Sinai, Egypt, 10th century BC - 7th century BC). The specific and contextual study of the 964 smallfinds found in the domestic structures of this site seeks to describe and create ways of interpreting the activities carried out by theinhabitants and their beliefs. They were recovered in systematic excavations, and analyzed and recorded under controlled laboratoryconditions (by the Argentine Archaeological Mission in Tell el-Ghaba since 1995). The analysis of this sample is carried out fromthe registration databases -field and laboratory registration sheets, photographs and drawings- and several related publications.This presentation proposes clear and operational tools to approach the study of the relationships between activities and materialculture, presenting categories in which the sample can be organized without referring to the functional question as the primary levelof object classification and hoping that this proposal can be applied at other archaeological sites in the eastern Mediterranean.